HUBUNGAN ANTARA RELIGIUSITAS DAN PERILAKU MEROKOK PADA LANSIA - Ade Dayu Darmawan; Emmanuel Satyo Yuwono (Journal of Innovation Research and Knowledge, 2025)
This study aims to determine the relationship between religiosity and smoking behavior in the elderly. Smoking behavior in the elderly can be risky for health, and religiosity is considered a factor that can influence this behavior. The method used in this study is quantitative correlational with data analysis using the SPSS program. The subjects of the study consisted of the elderly and had a tendency to smoke. The variables studied included religiosity as the independent variable and smoking behavior as the dependent variable. The results of the analysis using Kendall's correlation showed a significant negative relationship between religiosity and smoking behavior, with a correlation coefficient of -0.421 and a significance value of 0.000 (p <0.01). This shows that the higher a person's religiosity, the lower their tendency to smoke.